(untitled) (Research, Society and Development, 2023)
Urinalysis is the third most requested laboratory test by veterinarians. Because it is less invasive and cheap, in addition to adding to the early diagnosis of renal dysfunctions. Composed of physical, chemical and sediment exams. Thus, the main objective of the present work was to evaluate the importance of sedimentoscopy in relation to the normal values ​​obtained in the physical-chemical exams. The study was constituted from the epidemiological survey of the results of 137 urine tests performed at the Veterinary Clinical Center of UNIPAM. Among the analyzed groups, the offspring showed significant alterations in the parameters: protein 66.66% (2/3), scaly cells 66.66% (2/3) and bacteria 66.66% (2/3). In adults, protein 92% (23/25), bacterial flora 84% (21/25) and turbidity 92% (23/25). And in the elderly, alterations were observed for bacterial flora 78.78% (26/33), turbidity 81.81% (27/33), leukocytes 78.78% (26/33) and red blood cells 75.75% (25 /33). It was observed that 17 samples (12.41%) did not present physicochemical alterations. Of these, 64% had some indication of abnormality in the sediment examination, with high relevance if the pathological findings are analyzed separately. For various reasons of improper handling of urine, physical-chemical examinations may present incorrect results. Therefore, in sedimentoscopy the findings are reliable and contribute to the diagnosis.